Increased autophagy activity regulated by LC3B gene promoter DNA methylation is associated with progression to active pulmonary tuberculosis disease - Yung-Che Chen; Ying-Tang Fang; Chao-Chien Wu; Tung-Ying Chao; Yi-Hsi Wang; Chia-Cheng Tseng; Sum-Yee Leung; Chiu-Ping Lee; Ting-Ya Wang; Po-Yuan Hsu; Jen-Chieh Chang; Meng-Chih Lin; et al. (Respiratory Research)
Abstract Background This study aims to explore the role of autophagy-associated genes (ATG) and their epigenetic markers in the progression of mycobacterium tuberculosis (M. tb) infection, and to test the effects of de-methylation agents on macrophage functions against TB. Methods ATG expressions and their gene promoter DNA methylation levels of blood immune cells were measured in 60 patients with active pulmonary TB disease, 31 subjects with latent TB infection (LTBI), and 15 non-infected healthy subjects (NIHS). An in vitro monocytic THP-1 cell culture model under M. tb-specific antigen stimuli was applied. Results LC3B protein expression of blood M1/M2a monocyte, ATG5 protein expression of M2a, and mean DNA methylation levels of the LC3B gene promoter region of peripheral blood mononuclear cells were all increased in active TB patients versus either LTBI or NIHS group. The LC3B methylation levels were negatively correlated with its protein expressions. The discrimination of active TB disease from LTBI or NIHS was optimally captured by prediction scores, which combined LC3B (+) percentage of blood M1/M2a monocyte, LC3B gene promoter DNA methylation level, male gender, and body mass index. LC3B and ATG5 expressions of both blood M2a and neutrophil were decreased after 6-month anti-TB therapy, but hypermethylated LC3B gene promoter persisted. In vitro 5-Aza-2’-deoxycytidine treatment improved bactericidal, apoptosis and phagocytosis functions through augmenting autophagy flux via mechanisms other than demethylation of the LC3B gene promoter in THP-1 cells. Conclusions Increased LC3B expression and LC3B gene promoter hypermethylation may serve as biomarkers for progression of M. tb infection, while use of de-methylation agent may be a potential approach to host-directed immunotherapy in active TB disease.